Competitive Threats to Political Dynasty in Indonesia: The Failure of the Yasin Limpo Family in the 2018 South Sulawesi Gubernatorial Election - Meliala, Fransiskus Chandra Dwiputra; Permana, Panji Anugrah (Jurnal Politik, 2023)
Political scientists have studied the emergence and success of political dynasties in Southeast Asian countries, with post-New Order Indonesia providing several examples. Scholars have shown that Indonesia's political dynasties struggle to secure succession through local politics, but their analysis does not fully capture the turmoil of a political dynasty. This article analyzes the Yasin Limpo family's instability, focusing on how territorial politics has been exploited by local opposition and dynasties to seize and maintain power. This qualitative study provides a crucial means of understanding the success and failure of political dynasties. This article reveals that to monopolize power; political dynasties must rely not only on maximizing their dominance over the local territory but also on increasing their leverage in national politics. The Yasin Limpo family struggled to do so, facing a lack of national influence and internal family issues. Furthermore, local opponents successfully dismantled the political dynasty after bringing local political conflicts to the attention of national political elites.